2021
DOI: 10.3389/fcell.2021.725241
|View full text |Cite
|
Sign up to set email alerts
|

Tau and Membranes: Interactions That Promote Folding and Condensation

Abstract: Tau misfolding and assembly is linked to a number of neurodegenerative diseases collectively described as tauopathies, including Alzheimer’s disease (AD) and Parkinson’s disease. Anionic cellular membranes, such as the cytosolic leaflet of the plasma membrane, are sites that concentrate and neutralize tau, primarily due to electrostatic interactions with tau’s microtubule binding repeat domain (RD). In addition to electrostatic interactions with lipids, tau also has interactions with membrane proteins, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 149 publications
(256 reference statements)
0
27
0
Order By: Relevance
“…Among these proteins, we found that recombinant htau40 interacts with a handful of previously described proteins, including DNAJ (heat shock protein 40 kD), S100β, and bridging integrator 1 ( 37 , 38 , 39 , 40 ). Given the high affinity of the intrinsically disordered tau for many biomolecules ( 52 ), it is nevertheless surprising that we could detect only a relatively small number of polypeptides interacting with tau in vitro in our microarray chips. One explanation may be that recombinant proteins spotted on the chip might carry post-translational modifications of insect Sf9 cells, which may influence in vitro –binding features of the candidate polypeptides.…”
Section: Discussionmentioning
confidence: 99%
“…Among these proteins, we found that recombinant htau40 interacts with a handful of previously described proteins, including DNAJ (heat shock protein 40 kD), S100β, and bridging integrator 1 ( 37 , 38 , 39 , 40 ). Given the high affinity of the intrinsically disordered tau for many biomolecules ( 52 ), it is nevertheless surprising that we could detect only a relatively small number of polypeptides interacting with tau in vitro in our microarray chips. One explanation may be that recombinant proteins spotted on the chip might carry post-translational modifications of insect Sf9 cells, which may influence in vitro –binding features of the candidate polypeptides.…”
Section: Discussionmentioning
confidence: 99%
“…The association of Tau with the plasma membrane can occur directly through electrostatic interactions with anionic lipids 15,16 and indirectly through interactions with membrane-associated proteins, such as Fyn 5 , dynactin 17 , and annexin A2 18 . Moreover, Tau interacts with microtubules and actin filaments, anchoring them to the plasma membrane 10 . Despite the critical importance of Tau-membrane interactions, quantifying how Tau behaves and organizes at the plasma membrane in a native cellular environment has previously proven challenging, thereby limiting our understanding of how this protein executes its function in this compartment 11 .…”
Section: Mainmentioning
confidence: 99%
“…The association of Tau with the plasma membrane can occur directly through electrostatic interactions with anionic lipids 14,15 and indirectly through interactions with membrane-associated proteins, such as the Src kinase Fyn 16 , the motor protein dynactin 17 , and the phospholipid-binding protein annexin A2 18 . Moreover, Tau interacts with microtubules and actin filaments, anchoring them to the plasma membrane 19 . The question arises whether Tau forms aggregates near the plasma membrane, and if so, how stable these assemblies are.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membranes can regulate association and folding of intrinsically disordered proteins (IDPs), and affect aggregation propensities and functions of amyloid proteins. [17][18][19][20] Tau protein has been reported to interact with lipid membranes in vivo, [21][22][23][24] which may enhance its ability to stabilize microtubules and assist the localisation of organelles. For example, the combination of Tau protein with Golgi membranes can serve as a linker between Golgi and microtubules.…”
Section: Introductionmentioning
confidence: 99%